Study on Information Perception Based User Presence in Virtual Reality - QU Qian-wen, CHE Xiao-ping, QU Chen-xin, LI Jin-ru (Jisuanji kexue, 2022)
Virtual Reality(VR) technology builds a simulation environment through a computer,provides users with a three-dimensional dynamic view,and enhances the user's sensory experience,so that the user will get an immersive sense of immersion.With the rise and continuous development of virtual reality technology,people's visual and auditory experience has made great progress.With the development of multimedia technology,panoramic video emerges gradually.Compared with ordinary video,panoramic video has a wider viewing angle and richer visual information.The wide application of virtual reality technology and the development of panoramic video technology make virtual reality panoramic video(VR Video) become one of the most popular and concerned VR services.The information perception and acceptance behavior of users in the virtual reality environment have also been affected.Based on SMOTE algorithm,Bayesian network,logistic regression,and other statistical analysis methods and Few-shot Learning algorithm,this paper compares the differences in users' information memory degree,sense of reality,sense of participation,and other aspects when using VR head-mounted display and ordinary display iPad to watch panoramic video respectively.To explore the difference between the user's information acceptance effect and the sense of presence in the virtual reality environment and the traditional media environment.Experiments show that users with virtual reality headsets score an average of about 0.786 for message acceptance,compared with 0.634 for iPad users with regular displays.Among them,the score of positive information and non-positive information receiving effect in the virtual reality environment is 1.626 times and 1.245 times that of in the traditional environment respectively.However,it is noteworthy that in video A,which has the longest average scene duration,there is no significant difference in the information acceptance effect.In addition,the length of the user's visual residence time has a positive impact on the acceptance effect of information.After verifying that the sense of presence can be subdivided into the sense of reality and sense of participation,this paper shows that the score of users for the sense of presence in the iPad environment is always lower than that of in a VR environment through feature engineering and classification decision tree.After that,the correlation coefficient of the least square method is used to prove that presence has a positive effect on user information acceptance.Meanwhile,with the help of the Few-shot Learning algorithm,the average information memory number of video A－D is 9.20,9.13,8.83,and 10.57 when the sense of presence is strong,while the average information memory number of video A－D is 8.53,6.80,7.14 and 7.66 when the sense of presence is weak.It is proved that the user's sense of presence during information perception is beneficial to the user to obtain a better information acceptance effect.